PRESERVING HADITH TRADITION IN THE MODERN TIMES: Muhammad Yâsîn al-Fâdânî’s Thought on Sanad in His al-‘Ujâlah fi al-Ahâdîth al-Musalsalah - Noor, Umar Muhammad (Journal of Contemporary Islam and Muslim Societies, 2020)
Abstract: Before long after the completion of tadwîn (hadith canonization) in the 3/9 century, hadith transmission practice had become a formalistic tradition. The function of sanad (hadith’s chain of transmission) has shifted from being the authenticity determinant into a mere symbol of consecration. While most of modern Islamic reformists seem to undervalue the sanad, traditionalists groups perceive it as one of Islamic traditions that worth preservation. One of them was Muhammad Yâsîn al-Fâdânî (d. 1990), a prominent traditionalist whose name is often preceded by the title musnid al-‘ashr (the musnid of the century). The objective of this paper is to examine al-Fâdânî’s view on sanad and its significance in modern times with special attention given to both authenticity and preservation aspects. This study applies document and historical analysis focused mainly on al-Fâdânî’s al-‘Ujâlah fi al-Ahâdîts al-Musalsalah. It found that the sanad circulation in the modern period, including what is included in al-Fâdânî’s work, is not for theological or legal argument purposes. Instead, it was mainly maintained to preserve past Islamic tradition and to spread spirituality. Itcomes, however, with several negativities which draw serious criticism from both reformist and traditionalist groups. Keywords: hadith, sanad, musalsal, tabarruk, salafi